2020
DOI: 10.4236/jss.2020.84013
|View full text |Cite
|
Sign up to set email alerts
|

Housing Affordability and the Organized Private Sector Housing in Nigeria

Abstract: Growing housing deficit in Nigeria, particularly in urban areas, has resulted to various housing problems such as overcrowding, homelessness, slum and squatter developments. Despite the myriad of housing policies and programmes to solve the housing deficit, the desire goals have not been achieved, hence the adoption of organized Private Sector housing delivery in 2002. This research is an assessment of the Affordability of Organized Private Sector Housing Delivery in Nigeria. We adopted cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This is also in accordance with Muhammad (2016) who portrays that mortgage repayment, shortage of finance, effect of land use decree, and high cost of building materials are significant constraints to property investment decision. This result is also in line with finding of Okupe (2000) and Gumel (2000), who concluded that the factors that limit the number of property production include high cost of land, accessibility to finance, mortgage repayment, high cost of building materials, Government regulations and bye laws, cost of labour and inadequate facilities, improper distribution of funds and improper management. This further indicates that only investors with privilege and access to finance are in the real estate investment.…”
Section: 08supporting
confidence: 90%
See 1 more Smart Citation
“…This is also in accordance with Muhammad (2016) who portrays that mortgage repayment, shortage of finance, effect of land use decree, and high cost of building materials are significant constraints to property investment decision. This result is also in line with finding of Okupe (2000) and Gumel (2000), who concluded that the factors that limit the number of property production include high cost of land, accessibility to finance, mortgage repayment, high cost of building materials, Government regulations and bye laws, cost of labour and inadequate facilities, improper distribution of funds and improper management. This further indicates that only investors with privilege and access to finance are in the real estate investment.…”
Section: 08supporting
confidence: 90%
“…Unfortunately, the private sector is saddled with numerous problems which make supply always fall far short of demand and lower production quality (Nubi, 2008). Okupe (2000) and Gumel (2000), concluded that factors that limit the number of property production include high cost of land, accessibility to finance, mortgage repayment, high cost of building materials, Government regulations and bye laws, cost of labour and inadequate facilities, improper distribution of funds and improper management. In property business investors appreciate transparency of information and trustworthiness in a market.…”
Section: Constraints To Real Estate Investment Decisionsmentioning
confidence: 99%
“…Housing affordability encompasses a range of factors, including general housing affordability, purchase affordability, mortgage (repayment) affordability, income affordability, and rental affordability. Affordability is typically determined by examining the relationship between housing expenditure and household income, with a common threshold set between 25% and 30% of household income [32], [33]. Another approach, the residual income approach, considers whether a household's income, after deducting standard housing expenses, is sufficient to meet the minimum acceptable nonhousing expenses [33].…”
Section: Housing Affordabilitymentioning
confidence: 99%
“…Affordability is typically determined by examining the relationship between housing expenditure and household income, with a common threshold set between 25% and 30% of household income [32], [33]. Another approach, the residual income approach, considers whether a household's income, after deducting standard housing expenses, is sufficient to meet the minimum acceptable nonhousing expenses [33]. Housing affordability has many components and some are presented in Figure 1 [34].…”
Section: Housing Affordabilitymentioning
confidence: 99%
“…Affordable housing has economic and welfare effects on the development of a society. He postulated that economically, housing contributes mainly to the fixed capital formation, employment, and substantial backward and forward linkages with the rest of the economy [5,6]. Housing demand is described as the ability or willfulness of the consumer to pay for a particular place of habitation depending upon such consumer's income based on affordability, the house style, location preferences, and amenities.…”
Section: Introductionmentioning
confidence: 99%